The Relationship Between Christianity and the Evolution of Social Organization Systems in Modern China - LIU Shibo (Journal of Research for Christianity in China (JRCC), 2025)
This paper examines the influence and historical significance of Christianity’s eastward transmission on the legal framework of modern social undertakings in China. Drawing on examples from social anthropology and cultural anthropology, it analyzes the institutional development of social projects established by modern Christianity within China. These are contrasted with the institutional culture of indigenous traditional folk organizations and the traditional governance models prevalent in related social spheres.